“The Phoenix that was reborn from the flames”: the use of metaphor in historical writing in early Chilean Social History (1941-1953) (Palimpsesto, 2022)
This article presents four useful theoretical and methodological perspectives to analyze the use of metaphors in historical writing: hermeneutics, the theory of history, linguistics and historiography. These theoretical propositions are applied to the analysis of the Social History works produced in Chile between the 1940s and 1950s, verifying both the presence of metaphorical language in the tradition of professional writing inspired by Marxism, and the usefulness of metaphors. Represent historical phenomena particularly related to the condition of the working classes.
Keywords: Historiography; Metaphor; Social History; Historical Theory